Pierre Raymond - Švajncer, Marija (Anthropos (Ljubljana), 1989)
The relation between philosophy and science is one of the main questions in the quite extensive creative opus of the modern French philosopher Pierre Raymond (born 1942), a theoretician who problematically proceeded from Althusser's influence and first decides to take on the new subject of philosophical reflection - mathematics. By the pattern of neoposivistic tradition, he takes philosophy only as an auxilliary activity, as it is contradictory in itself, inside of it their is a cognitive contradiction between materialism and idealism which is actually affirened in their relation to science and in their distancing from ideology.
Keywords: filozofija; logika; philosophy; Raymond P.; logic